2001
DOI: 10.1038/eye.2001.52
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variation in fluorescein angiography induced nausea and vomiting

Abstract: Purpose A prospective survey was undertaken to investigate ethnic variations in the frequency of nausea and vomiting after fundus fluorescein angiography (FFA).Method Between May and September 1998, 197 adult patients were recruited to the study.A questionnaire containing closed-ended questions was completed by nurses after each

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…30 The incidence of mild adverse reaction is variable, for instance the incidence of nausea ranges between 0.8% 9 and 15%, 31 and vomiting ranges between 1% 32 and 4.2%. 4 Our results are at the low end of this range and consistent with the survey that found that 44% of all respondents estimated a frequency of nausea and vomiting in less than 1% of their patients. 2 Our study has a low rate of moderate adverse reactions compared with the major survey by Yannuzzi et al , 2 but the reason for this is unclear.…”
Section: Discussionssupporting
confidence: 91%
See 3 more Smart Citations
“…30 The incidence of mild adverse reaction is variable, for instance the incidence of nausea ranges between 0.8% 9 and 15%, 31 and vomiting ranges between 1% 32 and 4.2%. 4 Our results are at the low end of this range and consistent with the survey that found that 44% of all respondents estimated a frequency of nausea and vomiting in less than 1% of their patients. 2 Our study has a low rate of moderate adverse reactions compared with the major survey by Yannuzzi et al , 2 but the reason for this is unclear.…”
Section: Discussionssupporting
confidence: 91%
“…found no statistical difference in frequency of adverse reaction in patients with either normal or slow rate (injection lasting longer than 6 s) of fluorescein injection 3 . Previous FFA may result in higher incidence of adverse reaction in subsequent injection 4,16 . Kwiterovich et al.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…9 In other similar reports the incidence of mild reaction is variable, e.g., the incidence of nausea ranges between 0.8 10 and 15%, 11 and vomiting ranges between 1 12 and 4.2%. 13 In our study the overall rate of adverse reactions was 3.6% with nausea being the prevalent symptom (2.2%). All adverse reactions were mild in severity.…”
Section: Discussionmentioning
confidence: 45%